2016
DOI: 10.7566/jpsj.85.094713
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity and Non-Fermi-Liquid Behavior in the Heavy-Fermion Compound CeCo1−xNixIn5

Abstract: The effect of off-plane impurity on superconductivity and non-Fermi-liquid (NFL) behavior in the layered heavyfermion compound CeCo 1−x Ni x In 5 is investigated by specific heat, magnetization, and electrical resistivity measurements. These measurements reveal that the superconducting (SC) transition temperature T c monotonically decreases from 2.3 K (x = 0) to 0.8 K (x = 0.20) with increasing x, and then the SC order disappears above x = 0.25. At the same time, the Ni substitution yields the NFL behavior at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…These NFL features are quite similar to those seen in pure CeCoIn 5 , strongly suggesting that the NFL anomaly observed in Ni-doped CeCoIn 5 also originates from the AFM quantum critical fluctuations. Furthermore, the effective magnetic moment for x ≤ 0.3, estimated from the Curie-Weiss law at high temperatures, is nearly independent of x and coincides well with that calculated from the J = 5/2 multiplet in the Ce 3+ ion [39], suggesting that the Ce 4f electrons are mainly responsible for the magnetic properties in pure and Ni-doped CeCoIn 5 .…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…These NFL features are quite similar to those seen in pure CeCoIn 5 , strongly suggesting that the NFL anomaly observed in Ni-doped CeCoIn 5 also originates from the AFM quantum critical fluctuations. Furthermore, the effective magnetic moment for x ≤ 0.3, estimated from the Curie-Weiss law at high temperatures, is nearly independent of x and coincides well with that calculated from the J = 5/2 multiplet in the Ce 3+ ion [39], suggesting that the Ce 4f electrons are mainly responsible for the magnetic properties in pure and Ni-doped CeCoIn 5 .…”
Section: Introductionsupporting
confidence: 79%
“…A single crystal of CeCo 1−x Ni x In 5 with x = 0.25 was grown using an Indium flux technique, the details of which are described elsewhere [39]. The energy dispersive x-ray spectroscopy (EDS) and the inductively coupled plasma mass spectrometry (ICP-MS) measurements for the sample indicated that the actual Ni concentration approximately coincided with the starting (nominal) value within the deviation of ∆x/x ∼ 17%, including the experimental error.…”
Section: Experiments Detailsmentioning
confidence: 99%
See 3 more Smart Citations